Limited evidence of declining growth among moisture-limited black and white spruce in interior Alaska. Issue 1 (December 2017) - Sullivan, Patrick; Pattison, Robert; Brownlee, Annalis; Cahoon, Sean; Hollingsworth, Teresa
Abstract Boreal forests play critical roles in global carbon, water and energy cycles. Recent studies suggest drought is causing a decline in boreal spruce growth, leading to predictions of widespread mortality and a shift in dominant vegetation type in interior Alaska. We took advantage of a large set of tree cores collected from random locations across a vast area of interior Alaska to examine long-term trends in carbon isotope discrimination and growth of black and white spruce. Our results confirm that growth of both species is sensitive to moisture availability, yet show limited evidence of declining growth in recent decades. These findings contrast with many earlier tree-ring studies, but agree with dynamic global vegetation model projections. We hypothesize that rising atmospheric [CO2 ] and/or changes in biomass allocation may have compensated for increasing evaporative demand, leaving recent radial growth near the long-term mean. Our results highlight the need for more detailed studies of tree physiological and growth responses to changing climate and atmospheric [CO2 ] in the boreal forest.